The Role of Dendritic Cell Subsets and Innate Immunity in the Pathogenesis of Type 1 Diabetes and Other Autoimmune Diseases - Price, Jeffrey D.; Tarbell, Kristin V. (Frontiers in Immunology, 2015)
Dendritic cells (DCs) are key antigen presenting cells that have an important role in autoimmune pathogenesis. DCs control both steady-state T cell tolerance and activation of pathogenic responses. The balance between these two outcomes depends on several factors, including genetic susceptibility, environmental signals that stimulate varied innate responses, and which DC subset is presenting antigen. Although the specific DC phenotype can diverge depending on the tissue location and context, there are 4 main subsets identified in both mouse and human: conventional cDC1 and cDC2, plasmacytoid DCs, and monocyte-derived DCs. In this review, we will discuss the role of these subsets in autoimmune pathogenesis and regulation, as well as the genetic and environmental signals that influence their function. Specific topics to be addressed include: impact of susceptibility loci on DC subsets, alterations in DC subset development, the role of infection- and host-derived innate inflammatory signals, and the role of the intestinal microbiota on DC phenotype. The effects of these various signals on disease progression and the relative effects of DC subset composition and maturation level of DCs will be examined. These areas will be explored using examples from several autoimmune diseases but will focus mainly on type 1 diabetes.